Oxaliplatin but Not Irinotecan Impairs Posthepatectomy Liver Regeneration in a Murine Model - Perry A. Soriano; Nian Liu; Erick Castillo; Brock Foster; Avo Artinyan; Joseph Kim; Wendong Huang; Lawrence D. Wagman (International Journal of Hepatology)
Introduction. We examined the murine hepatectomy model of liver regeneration (LR) in the setting of neoadjuvant chemotherapy. Methods. C57BL/6 mice were randomized to receive neoadjuvant intraperitoneal (IP) injections of a control, oxaliplatin (15 mg/kg), or irinotecan (100 mg/Kg or 250 mg/Kg) solution. Hepatectomy (70%) was performed 14 days after the final IP treatment. Animals were sacrificed at postoperative day (D) 0, 1, 2, 3, and 7. Liver remnants and serum were collected for analysis. 𝑇-tests for independent samples were used for statistical comparisons. Results. For oxaliplatin, percent LR did not differ at D1 or D2 but was significantly less at D3 (89.0% versus 70.0%, 𝑃=0.048) with no difference on D7 (𝑃=0.21). Irinotecan-treated mice at both dose levels (100 mg/Kg and 250 mg/Kg) showed no significant differences in LR. BrdU incorporation was significantly decreased in oxaliplatin-treated animals (D1,2,3). Conclusions. Neoadjuvant oxaliplatin but not irinotecan impairs early LR in a posthepatectomy murine model which correlates with decreased DNA synthesis.